Iraqi Youth’s Usage of Alternative Media Platforms - Srahed, Jameel Naif; Al-Shijari, Siham Hassan (Al-Adab Journal, 2021)
The sequential developments in internet web contributed in creating this new form of media, The denotations and classifications of this new form of media increased for those who are concerned and experts in media; they called it several names: New Media, the alternative Media which comprises the hypothetical social webs, blogs, electronic forums, in addition to multiple types and forms, all this met by an increasing demand by the internet browsers worldwide. Some see it as an important means for engendering (bringing) human development within societies, a means for societal collaboration, approximating the notions and visions with the other, acknowledging the diverse cultures of other peoples, not to mention its effective and distinguished role as a successful communication means in the mass uprising and revolts. Hereby, emerges the significance of the relationship of the electronic interaction or interplay with the societal activities which comes to be considered as an imperative necessity for the youth generation in particular, since it is regarded as one of the youth collaborations sources and their participation in various societal and cultural fields. In fact, the societal collaboration is impossible without the youth’s contribution in it. In this respect, it is to be noted that the studies and field researches that are specialized in media gave a significant priority for the youth society in terms of its being a new society that owns its distinctive peculiarity. And hence came the need for the study of the nature and orientations of the youth towards the alternative media and more specifically, the internet webs and the social webs (Facebook). More importantly, the emergence of the social communication webs represented revolutionary conquest that led the media to move to unprecedented horizons and granted its users grand opportunities for influencing and moving beyond borders without limits and censorship, however with consideration for some relatively limits. Hence, this study aimed to bring to light the reality of the role that the alternative media plays in the treatment of the Iraqi society issues with a special and deliberate focus on the societal communication sites (Facebook) for its enormous and remarkable popularity on the global, Arabic and local level, And also because most of the vast majority of its users belong to the category age of the youth (who are the essential component of any societal and collaborative work), the researcher attempted to shed the lights on that serious role.